2010
DOI: 10.1002/etc.122
|View full text |Cite
|
Sign up to set email alerts
|

Contaminant pattern and bioaccumulation of legacy and emerging organhalogen pollutants in the aquatic biota from an e‐waste recycling region in South China

Abstract: Legacy pollutants, polychlorinated biphenyls (PCBs), dichlorodiphenyl trichloroethane and its metabolites (DDTs), and some emerging organhalogen pollutants, such as polybrominated diphenyl ethers (PBDEs), hexabromobenzene (HBB), pentabromotoluene (PBT), 2,3,4,5,6-pentabromoethyl benzene (PBEB), 1,2-bis (2,4,6-tribromophenoxy) ethane (BTBPE), and dechlorane plus (DP), were detected in an aquatic food chain (invertebrates and fish) from an e-waste recycling region in South China. Polychlorinated biphenyls, DDTs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
42
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 52 publications
9
42
2
Order By: Relevance
“…This result further demonstrated that e-waste recycling activities had an obvious influence on halogenated organic chemicals such as PCBs and PBDEs in the local river. This was in accordance with previous studies that characterized the e-waste recycling area as highly contaminated by PBDEs Zhang et al, 2010;Sun et al, 2012).…”
Section: Halogenated Flame Retardantssupporting
confidence: 93%
See 2 more Smart Citations
“…This result further demonstrated that e-waste recycling activities had an obvious influence on halogenated organic chemicals such as PCBs and PBDEs in the local river. This was in accordance with previous studies that characterized the e-waste recycling area as highly contaminated by PBDEs Zhang et al, 2010;Sun et al, 2012).…”
Section: Halogenated Flame Retardantssupporting
confidence: 93%
“…The exposure experiments in the laboratory revealed cyprinidae (common carp and tiger fish) and cichlidae (oscar fish) can debrominate some congeners with specific structures, for example BDE 99 and congeners with at least one metaor para-doubly flanked bromine atom, to form low bromiated congeners while no debromination occurred in catfish (redtail catfish, Phractocephalus hemiliopterus) (Zeng et al, 2012;Luo et al, 2013). The catfish (Clarias batrachus) collected in the e-waste recycling area, as in the present study, also exhibited a high BDE 99 abundance (Zhang et al, 2010). Plecostomus is a member of the catfish family; little or no debromination occurs in this fish species.…”
Section: Halogenated Flame Retardantsmentioning
confidence: 54%
See 1 more Smart Citation
“…Although BTBPE is used as a replacement of octa-BDE, the low detection frequency and concentration in hair and dust in the present study indicated that the environment in the study area might be less subject to this compound's contamination. Similar results were also found in aquatic biota and birds from the same area in our previous studies (Zhang et al, 2010).…”
Section: Non-pbde Bfrs Levels and Contaminant Patternsupporting
confidence: 91%
“…Following Hoh's study, several other reports have revealed that DP was present in numerous environmental matrix including air, dust, soil, water, and sediment (Jia et al, 2011;Ma et al, 2011;Qi et al, 2010;Qiu et al, 2007Qiu et al, , 2010Ren et al, 2008;Shen et al, 2011;Wang et al, 2010aWang et al, , 2010bYu et al, 2010), wildlife (Gauthier and Letcher, 2009;Guerra et al, 2011;Jia et al, 2011;Muñoz-Arnanz et al, 2011;Shen et al, 2011;Tomy et al, 2007;Wu et al, 2010;Zhang et al, 2010), and even human beings (Ren et al, 2009;Zheng et al, 2010) from various parts of the world, indicating the prevalence of this chemical in the environment. The detection of DP in the sediment cores (Hoh et al, 2006;Qiu et al, 2007) suggested the environmental persistence of this compound.…”
Section: Introductionmentioning
confidence: 92%